Modeling of the fracture energy on the finite element simulation in Ti6Al4V alloy machining. - Bermudo-Gamboa, Carolina; Andersson, Tobias; Svensson, Tobias; Trujillo-Vilches, Francisco Javier; Martín-Béjar, Sergio; Sevilla-Hurtado, Lorenzo (SpringerNature, 2021)
One of the main problems that exists when working with Finite Element Methods (FEM) applied to machining processes is the lack of adequate experimental data for simulating the material properties. Moreover, for damage models based on fracture energy, the correct selection of the energy value is critical for the chip formation process. It is usually difficult to obtain the fracture energy values and requires complex tests. In this work, an analysis of the influence of this fracture energy on the cutting force and the chip generation process has been carried out for different sets of cutting parameters. The aim is to present an empirical relationship, that allows selecting the fracture energy based on the cutting force and cutting parameters. The work is based on a FEM model of an orthogonal turning process for Ti6Al4V alloy using Abaqus/Explicit and the fracture energy empirical relation. This work shows that it is necessary to adjust the fracture energy for each combination of cutting conditions, to be able to fit the experimental results. The cutting force and the chip geometry are analyzed, showing how the developed model adapts to the experimental results. It shows that as the cutting speed and the feed increase, the fracture energy value that best adapts to the model decreases. The evolution shows a more pronounced decrease related to the feed increment and high cutting speed.
Keywords: Método de los elementos finitos; Mecanización; Mecánica de fractura; Aleaciones; Fracture Energy; Finit elements; Ti6Al4V; Dry machining; Aeronautical alloys